Special Courts as Nigerian Criminal Justice Response to the Plight of Awaiting Trial Inmates in Ebonyi State, Nigeria - Onyejegbu, Chukwuemeka Dominic; Onwuama, Emeka M.; ONAH; Chijioke, Celestine; Okpa, John Thompson; Ajah, Benjamin Okorie (International Journal of Criminology and Sociology, 2021)
This study looks at how using special courts can provide succor to the plight of awaiting trial inmates in Ebonyi state, Nigeria. The study adopted quantitative and qualitative research methods, with a sample of 1,498 respondents comprising 617 police officers, 623 awaiting-trial inmates, 113 court staff, and 145 prison officers drawn from Ebonyi State. Purposive and Multi-stage sampling techniques were used to reach the respondents. The quantitative data was descriptively analyzed using percentages and charts, while a thematic method of analysis was employed in the qualitative data. The findings revealed that, while there has been an uptick in awaiting trial problems, there is no meaningful provision to address them, despite the existence of provisions within the Nigerian legal framework. The article calls for the creation of special courts that are equipped to address peculiar crime cases in a more effective and faster manner. These courts are better poised to address the peculiarities of special cases and pass better and faster judgments.